Nanotechnology and Treatment of Cardiovascular Disease: A Review of Nanoscale Innovations for Regenerative Therapy - M. Connell, John; S. Tim, Dominique (Current Nanomedicine, 2016)
Background: Cardiovascular disease is a major cause of morbidity and mortality worldwide. In particular, heart failure remains a widespread disease with few effective treatment options. Medical management with traditional pharmaceutical and surgical methods have had limited success at relieving symptoms or prolonging life. Therefore, new treatment options have undergone vigorous research. Methods: We searched for reports of recent advances in the use of nanotechnology for stem cell therapy for the treatment of cardiovascular disease. We focused on the use of nanotechnology to improve stem cell culturing, tissue engineering, and tissue imaging post-cell implantation. Results: Nanotechnology, in the form of spun or chemically assembled nanofibers, has been used to create a three-dimensional structure to support the growth of stem cells and promote their differentiation into functional myocardium. The addition of growth and signaling factors such as insulin-like growth factor 1 (IGF1) or vascular endothelial growth factor (VEGF) to these fibers has also improved stem cell development. For imaging, and tracking cells after implantation, nanoscale fluorescent tags such as NaYF4 nanocrystals doped with Yb3+,Er3+ have been shown to be effective. Carbon nanotubules have also been shown to be effective for following stem cell position in vivo. Conclusion: Nanotechnology has enhanced stem cell-based regenerative therapy, aiding with the ex vivo culturing and differentiation of stem cells as well as with in vivo cell tracking and monitoring. Future advances in nanotechnology will likely produce significant changes in the methods and practice of regenerative cell therapy.
Keywords: Cardiovascular